Peningkatan Kualitas Pendidikan Sekolah Dasar Islam Amanah Kekait Melalui Kemah Bakti Masyarakat Mahasiswa - Mohammad Archi Maulyda; Muhammad Tahir; Arif Widodo; Deni Sutisna; Radiusman Radiusman; Muhammad Syazali; Muhammad Sobri (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Community Service Camp (KBM) is a PGSD student activity as a form of implementation of one of the Higher Education Tri Dharma values namely Community Service. This activity is a routine activity that is carried out once a year. For the 2020 period, KBM activities will be carried out in Batu Butir Village, Kekait District, North Lombok Regency. This activity lasted for 1 month starting on January 2 to February 2, 2020. One of the sub-units of this activity was an effort to improve the quality of education in SDI "Amanah" Kekait. This activity was carried out because based on problem mapping, the school still lacked teacher education personnel. In addition, the teacher who teaches is also not in accordance with the scientific field in elementary schools. The second problem is the lack of parental insight regarding the urgency of education for children. This can be seen from the many children in Batu Butir Village who attend school only up to elementary school level. Therefore the PGSD PKM team carried out two main activities, namely (1) Helping to teach at school; and (2) Education the importance of education for children. This activity received a positive response from students and guardians of students. The results of the first activity show that students become active and enthusiastic in learning. In addition the value obtained also increased. For the second activity, many dialogues conducted with the parents showed that parents began to be enthusiastic in sending their children to high school.